Advances in command, control & communication systems - Harris, C. J. (Christopher John).; White, I. Ph.D. (Ian). (London, United Kingdom Institution of Engineering and Technology, 1987)
This book describes some of the developments in Command, Control and Communication (C3) systems. The topics cover the design of large real-time man-machine systems, which are now a vital area of intensive scientific and financial investment. C3 systems are for complex resource management and planning, and although this has a predominantly military connotation, similar systems are now developing in civil sector applications, public utilities and banking. Topics discussed include the design and structure of C3 systems, databases, standards, the man-machine interface and advanced processing including the sensor data fusion and artificial intelligence.
Electronic reproduction.
Keywords: Command and control systems; Electronic books